Britta Maria Colligs, Material Ecocriticism and Sylvan Agency in Speculative Fiction: The Forests of the World, Lexington Books, 2023, 218 p. - DRAGOȘ, Adina (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Our understanding of ecocritical issues often tends to revolve around the preservation of various ecosystems affected by disasters such as pollution or climate change—and for good reason. In many aspects, papers have shown that human intervention has been a double-sided sword in the ecological development of the world, as conservation efforts remain high in the face of decades of sylvan exploitation at the hands of the Northern hemisphere, is what Britta Marie Colligs points out in her study, Material Ecocriticism and Sylvan Agency in Speculative Fiction. By taking a look at the literature of the past century, Colligs manages to reconfigure our understanding of ecocriticism not from an Anthropocene perspective as has often been the case, but rather by proposing that we dispel portrayals of the environment as an object to be saved, but rather as an entity that expresses its own agency. Published in 2024, the book is an incursion into man’s literary relationship with the environment, specifically forest areas and how its portrayal affected our own understanding of humanity along with that of the post-Anthropocene. In order to achieve this, Colligs set out to analyse arboreal characters and realms belonging to the speculative fiction genre through the lens of ecocriticism, ranging from works such as those of J.R.R. Tolkien, Ursula K. Le Guin to those of George R.R. Martin, J.K. Rowling and Christopher Paolini. By offering such a comprehensive look at many classics of this particular genre, she seeks to define what contemporary fiction’s relationship with the sylvan environment means in the current climate, as well as the many aspects that tend to be shared among these works.